Sacre bleu eaudiobook A comedy d'art. - Moore, Christopher (Recorded Books Inc., 2012)
New York Times best-selling author Christopher Moore's delightfully irreverent novels combine sly humor and rampant silliness. In the tradition of Fool and Lamb, SacrE Bleu casts Moore's view askance on a familiar subject and twists it into something wholly original. Famed painter Vincent van Gogh lies dead, an apparent suicide victim. Two of his painterly colleagues are not convinced that the artist truly offed himself, though, so they embark on a quest to find the truth.